EVALUATION OF ECOLOGICAL IMPORTANCE OF MYSIDS AS A FOOD ITEM IN THE DIET OF FISH, NEW ZEALAND - Punchihewa, N. N. (International Journal of Environment, 2015)
The main objective of this study is to determine the ecological importance of mysids as a food item of selected fish species using C and N isotopes (stable isotopic study) and gut content analysis of fish. Fish samples (Galaxias maculates and Athrinidae sp.) and mysid samples (Tenagomysis chiltoni and T. novaezealandiae) were collected from Kakamatua Stream situated on the west coast of Auckland region in late January 2009 (summer). All the collected samples were oven-dried, and then ground to obtain a homogeneous powder. Three replicates of each sample were prepared. Samples were processed by the Waikato Stable Isotope Unit (Scientific/20). For gut content analysis, ten specimens of each fish species, G. maculates and Athrinidae sp. were collected and were fixed in 5% formalin immediately. These fish specimens were dissected out and the stomach contents were mixed in a beaker with 10 ml water. After mixing, the contents were examined under the light microscope fitted with an eye piece micrometer. It is evident from both methods that two mysid species T. chiltoni and T. novaezealandiae form a substantial component of the diet of commercially important G. maculates, at Kakamatua stream. Changes in the diet, during the ontogenetic development, in relation to body size have shown a significant enrichment of ?15N values and ?13C values of T. chiltoni and G. maculates. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 35-41